British Merchants in New Markets: The Case of Wylie and Hancock in Brazil and the River Plate, C. 1808-19 - Llorca-Jana, M (Routledge, 2014)
In 1808, after the Portuguese royal family was forced to leave Portugal and move to Brazil, Brazilian ports were opened to British merchant houses, which were quick to open offices in the likes of Bahia and Rio de Janeiro. By 1810 there were probably over 200 British merchant houses operating in Brazil, but we know very little about them because most of their historical records have not survived. In addition, scholars have assumed that, on account of the dominant British economic power, the establishment of new mercantile houses in South America c. 1808-19 was an easy task. This assumption is challenged in this paper, which sheds new light on the activities of one of these British merchant houses, making use of a recently discovered business collection concerned with the activities of Wylie & Hancock, a Scottish house which operated in Brazil and the River Plate from 1808 to 1819. These papers also provide a unique insight into neglected topics such as: the nature of managerial mercantile organisations; what the economic actors at the time actually did and thought; and how strategic and tactical choices were reached. © 2013 © 2013 Taylor & Francis.